Strategi Perencanaan Investasi untuk Meningkatkan Kesejahtraan Masyarakat - Manek, Esmeralda; Ikun, Ernestus; Florencia Virginia Nai Boro; Leonardus Nama Bailamen; Irvan Reynaldy A. Nahak; Adelheid Elisabet Loda; Joaquina Felicia Saru (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to examine effective investment planning strategies to improve community welfare, focusing on capital efficiency using the Incremental Capital Output Ratio (ICOR) indicator, human capital development, and enhancing the competitiveness of local economic sectors. The research method used is a qualitative literature review, which shows that a low ICOR value indicates high investment efficiency, driving optimal economic growth. Case studies in various regions, such as West Nusa Tenggara, Papua, and Palangka Raya, emphasize the importance of ICOR in allocating capital investment efficiently and productively. Additionally, improving the quality of human capital contributes to increased productivity, innovation, and investment absorption capacity, which in turn supports economic growth. Strengthening key economic sectors is also crucial in attracting investments that have a broad positive impact. In conclusion, the integration of capital efficiency, human capital development, and enhancing the competitiveness of local economic sectors in investment strategies plays a vital role in accelerating inclusive and sustainable economic growth and improving overall community welfare.